The alterities of modernity: Buenos Aires 1880-1910 - Gayol, Sandra (1998)
It was the 1870s and Buenos Aires managed to break the general impression of a still typically colonial city. The rural aspect and the peasant atmosphere, that peculiar air of outside the walls that invaded the visitor when he left the center, the insufficiencies of an urban structure lacking drinking water, electricity, pavements, means of transport... the behaviors so little " civilizations" of such little "working" inhabitants... supported the conviction in the leading sectors - landowners, professionals and merchants who administered the city and directed the nation - that everything was still to be done. To change the course, these men did not hesitate to prioritize the measures: the replacement and increase of the population.